2020
DOI: 10.1038/s42003-020-01262-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning assistive rapid, label-free molecular phenotyping of blood with two-dimensional NMR correlational spectroscopy

Abstract: Translation of the findings in basic science and clinical research into routine practice is hampered by large variations in human phenotype. Developments in genotyping and phenotyping, such as proteomics and lipidomics, are beginning to address these limitations. In this work, we developed a new methodology for rapid, label-free molecular phenotyping of biological fluids (e.g., blood) by exploiting the recent advances in fast and highly efficient multidimensional inverse Laplace decomposition technique. We dem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Next, we used a 2D-NMR sparse sampling method (2D-NMR with fast acquisition) which provides similar results within a shorter time frame than conventional T 1 /T 2 correlations experiments. A recent study reported that water peaks (A-ratio) in the T 1 /T 2 correlation spectra can be used to predict the degree of water-protein interactions in the fibrinogen-plasma system 17 . Compared to plasma fibrinogen control (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we used a 2D-NMR sparse sampling method (2D-NMR with fast acquisition) which provides similar results within a shorter time frame than conventional T 1 /T 2 correlations experiments. A recent study reported that water peaks (A-ratio) in the T 1 /T 2 correlation spectra can be used to predict the degree of water-protein interactions in the fibrinogen-plasma system 17 . Compared to plasma fibrinogen control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Increased water-protein interactions drastically reduce the motion of the water proton, leading to reduced relaxation times for T 1 and T 2 . It appears that T 2 relaxation is more effective than T 1 relaxation 17 . Fibers are formed when fibrinogen monomers aggregate into protofibrils, resulting in structural heterogeneity within the fibrin gel 38 , 41 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To further de ne water-protein interactions, including the hydration of bers via water-water proton interaction, we next de ned T 1 /T 2 ratio as A-ratio to predict the degree of water-protein and/or water-water interactions as previously described 17 . Control plasma solutions demonstrated an A-ratio = 57.2 (Fig.…”
Section: Oxidation Alters T 2 Relaxation Of Water Protons In Brinogenmentioning
confidence: 99%
“…Molecular ngerprints of complex biological uids such as blood have been encoded using two-dimensional (2D) T 1 /T 2 correlations. NMR relaxometry has been used to investigate oxygenated (oxy-Hb), deoxygenated (deoxy-Hb) and oxidized (oxidized Hb) hemoglobin (Hb) derivatives with respect to their altered T 1 /T 2 relaxation states 17 . Spin-spin (T 2 ) relaxation times have also been used to probe brin clot structure via paramagnetic properties of hemoglobin in erythrocytes entrapped within whole blood clots [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%